Psychometric Properties of the Arabic Version of the Wakeman Emotional Intelligence Questionnaire - Al-Shayeb, Abdelhafez (Jordan Journal of Educational Sciences, 2010)
This study aimed at adapting and validating an Arabic version of the Wakeman Emotional Intelligence Questionnaire (EIQu) for Jordanian university students. The data were collected from 620 male and female undergraduate students from different academic levels at Al al-Bayt University in Jordan in the academic year 2007/2008. Item analysis revealed an acceptable discrimination and difficulty indices. Construct validity has been investigated through examining the questionnaire factor structure, and testing the hypothesis concerning the mean score differences among the four academic levels, as well as the hypothesis concerning the relationship between each subscale scores and student grade point average. The results of the factor analysis identified two major factors: noncognitive self-management and social dexterity. Two-way ANOVA results revealed significant mean score differences on each subscale due to the academic level variable. The results also revealed significant correlation coefficients between scores on each subscale and academic achievement. It has been found that the internal consistency and stability coefficients were significant.